Knowledge about oral health in older adults from a medical office in Ciego de Ávila - Wendy Guerra López; Lina Isabel Torres Gárriz; Evelyn Sardiñas Montero; Yenise García Aldave; Daniela Rivas Torres; Marcos Daniel Estrada López (Medisur)
Foundation: population aging is one of the main challenges for most countries. In the context of dental services, this brings with it an increase in geriatric patients in need of dental care. Objective: determine the level of knowledge about oral health in older adults from the Family Medical Office Number 3 of the Belkis Sotomayor Polyclinic. Methods: a descriptive study was carried out from March to August 2023. The universe was made up of the population over 60 years of age belonging to the Family Medical Office No. 3 (242 patients), in the Ciego de Ávila municipality, and the sample was 120 patients, selected through simple random sampling. A questionnaire validated by five experts in the stomatology area was applied. Absolute numbers and percentages were used as measurements. Results: 68.3% of older adults presented difficulties in the questions about performing oral self-examination. 67.5% of them answered the questions about periodontal diseases incorrectly, because they did not consider ailments related to the gums as harmful to oral health. 40.0% of the participants reported that inappropriate habits, such as smoking, cause alterations in the oral cavity. Conclusions: it was determined that the level of knowledge of these older adults was regular, which shows that strategies must be intensified to increase the health culture in this group.